Optical micro-tomography “OPenT” allows the study of large toadfish Halobatrachus didactylus embryos and larvae - M. Félix, Pedro (2019)
Batrachoidids, which include midshipman and toadfish are less known among embryologists, but are common in other fields. They are characteristic for their acoustic communication, and develop hearing and sound production while young juveniles. They lay large benthic eggs (>5 mm) with a thick chorion and adhesive disk and slow development, which are particularly challenging for studying embryology. Here we took advantage of a classical tissue clearing technique and the OPenT open-source platform for optical tomography imaging, to image a series of embryos and larvae from 3 to 30 mm in length, which allowed detailed 3D anatomical reconstructions non-destructively. We documented some of the developmental stages (early and late in development) and the anatomy of the delicate stato-acoustic organs, swimming bladder and associated sonic muscles. Compared to other techniques accessible to developmental biology labs, OPenT provided advantages in terms of image quality, cost of operation and data throughput, allowing identification and quantitative morphometrics of organs in larvae, earlier and with higher accuracy than is possible with other imaging techniques.